Best Practices or Best Guesses? Assessing the Efficacy of Corporate Affirmative Action and Diversity Policies - Kalev, Alexandra; Dobbin, Frank; Kelly, Erin (American Sociological Review, 2006)
Employers have experimented with three broad approaches to promoting diversity. Some programs are designed to establish organizational responsibility for diversity, others to moderate managerial bias through training and feedback, and still others to reduce the social isolation of women and minority workers. These approaches find support in academic theories of how organizations achieve goals, how stereotyping shapes hiring and promotion, and how networks influence careers. This is the first systematic analysis of their efficacy. The analyses rely on federal data describing the workforces of 708 private sector establishments from 1971 to 2002, coupled with survey data on their employment practices. Efforts to moderate managerial bias through diversity training and diversity evaluations are least effective at increasing the share of white women, black women, and black men in management. Efforts to attack social isolation through mentoring and networking show modest effects. Efforts to establish responsibility for diversity lead to the broadest increases in managerial diversity. Moreover, organizations that establish responsibility see better effects from diversity training and evaluations, networking, and mentoring. Employers subject to federal affirmative action edicts, who typically assign responsibility for compliance to a manager, also see stronger effects from some programs. This work lays the foundation for an institutional theory of the remediation of workplace inequality.